Correlation between mechanical dissipation and improved X-band electromagnetic shielding capabilities of amine functionalized graphene/thermoplastic polyurethane composites - Nasr Esfahani, Azam; Katbab, Ali Asghar; Taeb, Aidin; Simon, Leonardo; Pope, Michael (Elsevier, 2017)
Graphene-based polymer nanocomposites have demonstrated significant promise to create commercially viable electromagnetic interference (EMI) shielding to protect the next-generation of electronic materials from radiative pollution. In the present study, we carry out a systematic analysis of the dynamic mechanical, dielectric, electrical and X-band shielding properties of thermoplastic polyurethane (TPU) elastomer filled with amine functionalized graphene obtained by the rapid thermal expansion of graphite oxide. By preparation of nanocomposites based on modified and unmodified graphene using solution mixing and hot compression moulding, we demonstrate that the modification with 2-aminoethyl methacrylate enhances the EMI shielding from 14 to 25 dB. We also show by fracture analysis, cross-sectional transmission electron microscopy and dynamic mechanical analysis that the modification significantly strengthens the interfacial interactions between TPU and the functionalized graphene at the same filler loading. We find that the dominant shielding mechanism is through absorption and discuss the correlation between the viscoelastic mechanical loss tangent and the more effective dissipation of absorbed EM radiation which might account for the discrepancy between the theoretically predicted and experimentally observed EMI SE.
The final publication is available at Elsevier via http://dx.doi.org/10.1016/j.eurpolymj.2017.08.038 © 2017. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: Thermoplastic polyurethane; Graphene; Electromagnetic interference shielding; Viscoelastic properties; Interfacial interaction